Assessing Long‐Term Changes in Regional Groundwater Recharge Using a Water Balance Model for New Mexico. (27th July 2021) - Li, Xiaojie; Fernald, Alexander G.; Kang, Shaozhong
Abstract: In New Mexico in the arid southwestern United States, groundwater recharge is crucial to sustain groundwater (GW), which is vitally important to life, agriculture, industry, and ecosystems. To better understand the changes in recharge statewide, we explored the changes in groundwater recharge (RE), precipitation ( P ), surface water inflow (SWin ), outflow (SWout ), diversions (SWdiv ), returns (SWret ), and surface water and GW evapotranspiration (SWE and GWET ) in five New Mexico counties: Taos, Torrance, Doña Ana, Eddy, and Lea during 1975–2015. The results show that the change‐point of RE was in the 1990s, leading to contrasting tendencies in RE before and after the change‐point with a decreasing rate during the latter one. There was a significant positive relationship between RE and P for Taos. The highest contribution rate (CR) to RE was SWout for Taos, whereas GWET ranked as the top CR for the other counties. Furthermore, the annual CR of GWET to RE increased significantly in all counties except Lea. The above results reveal that P and surface water flows played the dominant role in impacting RE in northern New Mexico where surface water is the primary local water resources, whereas GWET had the highest and increasingly continuous influence in central and southern New Mexico where the surface water is much less than that in northern New Mexico. This study shows that water budgets are important to identify differences in regional hydrological regimes that affect planning to maintain RE to groundwater. Abstract : Research Impact Statement : Groundwater recharge changes and their hydrological contributors are distinct in different regions of New Mexico during 1975–2015. Managing land and water could provide future recharge sustainability.